Manipulating acoustic and plasmonic modes in gold nanostars. Issue 7 (6th June 2019) - Chatterjee, Sharmistha; Ricciardi, Loredana; Deitz, Julia I.; Williams, Robert E. A.; McComb, David W.; Strangi, Giuseppe
Abstract : In this contribution experimental evidence of plasmonic edge modes and acoustic breathing modes in gold nanostars (AuNSs) is reported. AuNSs are synthesized by a surfactant-free, one-step wet-chemistry method. Abstract : In this contribution experimental evidence of plasmonic edge modes and acoustic breathing modes in gold nanostars (AuNSs) is reported. AuNSs are synthesized by a surfactant-free, one-step wet-chemistry method. Optical extinction measurements of AuNSs confirm the presence of localized surface plasmon resonances (LSPRs), while electron energy-loss spectroscopy (EELS) using a scanning transmission electron microscope (STEM) shows the spatial distribution of LSPRs and reveals the presence of acoustic breathing modes. Plasmonic hot-spots generated at the pinnacle of the sharp spikes, due to the optically active dipolar edge mode, allow significant intensity enhancement of local fields and hot-electron injection, and are thus useful for size detection of small protein molecules. The breathing modes observed away from the apices of the nanostars are identified as stimulated dark modes – they have an acoustic nature – and likely originate from the confinement of the surface plasmon by the geometrical boundaries of a nanostructure. The presence of both types of modes is verified by numerical simulations. Both these modes offer the possibility of designing nanoplasmonic antennas based on AuNSs, which can provide information on both mass and polarizability of biomolecules using a two-step molecular detection process.